An Innovation of High-Energy and Protein Biscuits Made of Black Rice Flour Substituted With Mung Bean Flour - Fathonah, Siti; Rachmawati, Rina; Rosidah, Rosidah; Kristanti, Bela Siska; Iswari, Retno Sri (Universitas Negeri Semarang, 2020)
This study was aimed to determine the public acceptance and the nutritional contents of the black rice flour biscuits substituted with mung bean flour. A completely randomized design with various amount of substituted mung bean flour (MBF) in the black rice flour (BRF) biscuits was used as the experimental design. The ratios of the BRF-to-MBF were 60: 20; 50: 30, and 40:40. The acceptance test used was the hedonic test with the lowest and the highest scores of 1 and 9, indicating “extremely unfavorable” and “extremely favorable” criteria, respectively. The content of carbohydrates (using Luff School method), ash (using the dry method), protein (using Kjeldahl method), water (using oven drying methods), crude fiber (using the gravimeter method), lipids (using the Soxhlet extraction method), and anthocyanins (using the pH-differential method) was determined and evaluated. The analysis of differences in the acceptability of the biscuits was performed using an ANOVA test, followed by the Tukey HSD test. The results showed that there were differences in people's acceptance of black rice flour biscuits substituted with mung bean flour for the overall indicators, i.e., the color and taste of the black rice biscuits. The most preferred biscuits were biscuits with a composition of 40% black rice flour and 40% substituted mung bean flour with a mean value of 7.2. The nutritional content of the black rice biscuits was as follows: the content of energy of 447- 465 kcal, carbohydrates of 58.4-60.9%, protein of 7.14-9.15%, lipids of 20.3-22.2%, ash of 2.3%, moisture of 5.25-8.65%, fiber of 1.3-2.3% and anthocyanin of 20-37ppm. The production of BRF40: MBF40 (40% black rice flour and 40% mung bean flour) biscuits was highly recommended, in addition to the optimum baking time as the future work.